The Herľany geyser – a unique hydrogeological and geotouristic locality in Europe - Štrba, Ľubomír (Geotourism/Geoturystyka, 2017)
The paper introduces the Herľany geyser as a unique geotouristic locality that would be appreciated as a member of any geosite network. Based on description of general geology and hydrogeology of the area, the text explains the origin of the cold-water geyser. Applying the method of geosites assessment, detailed geotouristic value of the geyser is specified for the first time.